Transcranial direct current stimulation (tDCS) targeting the postcentral gyrus reduces malevolent creative ideation. Issue 1 (24th March 2023) - Gao, Zhenni; Lu, Kelong; Hao, Ning
Abstract: Malevolent creativity (MC) is defined as a manifestation in which people propose to materially, mentally or physically harm themselves or others in a novel manner. Malevolent creative ideation can be inhibited by high moral emotions (i.e. sympathy, guilt and shame) and low negative emotions, which promote prosocial behaviors. Given that the right postcentral gyrus (PCG) is involved in generating sympathy and emotional recognition for others and the right middle frontal gyrus (MFG) is involved in emotional regulation, we suggest that the right PCG and right MFG may play important roles in malevolent creative ideation. In Study 1, we recruited 98 healthy and right-handed college participants (80 females, age = 21.11 ± 2.00 years) and examined the role of the right PCG in malevolent creative ideation using transcranial direct current stimulation (tDCS). The results showed that the accuracy of emotional recognition changed when the right PCG received electrical stimulation. Enhancing the activation of the right PCG reduced MC originality and fluency, whereas inhibiting it increased MC originality and fluency. In Study 2, we recruited 91 healthy and right-handed college participants (74 females, age = 21.22 ± 2.28 years) and examined the role of the right MFG in malevolent creative ideation using tDCS. The results showed no significant difference in malevolent creative performance between the pre- and post-test when electrical stimulation was applied over the right MFG. These findings indicate that enhancing the activation of the right PCG, which is closely correlated with emotional recognition, reduces an individual's malevolent creative ideation.